Racial/Ethnic Disparities in Diabetes Quality of Care: The Role of Healthcare Access and Socioeconomic Status - Canedo, Juan R. (J Racial Ethn Health Disparities, 2017)
INTRODUCTION: Blacks, Hispanics, and Asians are disproportionately affected by diabetes. We assessed the state of racial/ethnic disparities in diabetes quality of care in the U.S. METHODS: We analyzed cross-sectional data of adults diagnosed with Type 2 diabetes in the nationally-representative 2013 Medical Expenditure Panel Survey. Differences in adherence to five diabetes quality of care recommendations (HbA1c twice yearly; yearly foot exam, dilated eye exam, blood cholesterol test and flu vaccination) were examined by race/ethnicity while controlling for three social determinants of health (health insurance status, poverty, and education) and other demographic variables. RESULTS: Among adults with diabetes in the U.S., 74.9% received two or more HbA1c tests, 69.0% had a foot exam, 64.9% had an eye exam, 85.4% had a cholesterol test, and 65.1% received flu vaccination in 2013. Compared to Whites, all were lower for Hispanics; HbA1c tests, eye exam, and flu vaccination were lower for Blacks; HbA1c tests, foot exam, and eye exam were lower for Asians. In adjusted models, the only remaining disparities in quality of care indicators were: HbA1c tests for Hispanics (AOR 0.67, CI=0.47 - 0.97), Blacks (AOR 0.59, CI=0.40 - 0.88), and Asians (AOR 0.47, CI=0.42 - 0.99); foot exams for Hispanics (AOR 0.65, CI=0.47 - 0.90) and flu vaccination for Blacks (AOR 0.68, CI= 0.49 - 0.93). CONCLUSION: Lack of insurance coverage and education explained some of the racial/ethnic disparities observed in diabetes quality of care. Improving quality of diabetes care could help reduce rates of diabetes complications, healthcare costs and mortality.